Audit quality of the coal mining companies listed on the Indonesian stock exchange - Sitanggang, Tikkos (Technium Social Sciences Journal, 2023)
This study aims to determine the influence of audit fee, audit tenure, and audit rotation on audit quality in coal mining companies listed on the Indonesian Stock Exchange for the period 2017 to 2021. The population of this study totaled 47 companies and the purposive sampling method resulted in 12 companies or 60 firms-years for analysis. This research is a quantitative study using secondary data in the form of annual financial reports from sample companies. Based on the test results show that audit fee has a positive effect on audit quality, meanwhile audit tenure and audit rotation have no effect on audit quality.